2022
DOI: 10.1186/s12905-022-01996-4
|View full text |Cite
|
Sign up to set email alerts
|

Positive intervention effect of mobile health application based on mindfulness and social support theory on postpartum depression symptoms of puerperae

Abstract: Objective This study investigated the effects of mobile health application designed based on mindfulness and social support theory on parenting self-efficacy and postpartum depression symptoms of puerperae. Methods We recruited 130 puerperae from a hospital in China and randomized them to an App use group (n = 65) and a waiting control group (n = 65). The App group underwent an 8-week app use intervention while the control group underwent no interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Previous research showed that mindfulness can have a positive impact on different populations. For example, increasing mindfulness among clinicians can improve the safety competence of medical staff (Braun et al, 2019 ), patients (Liu et al, 2022b ), employees (Liu et al, 2022c ), and flight attendants (Liu et al, 2022d , e ). It has also been demonstrated that mindfulness is an effective method for coping with COVID-19-related stress (Weis et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research showed that mindfulness can have a positive impact on different populations. For example, increasing mindfulness among clinicians can improve the safety competence of medical staff (Braun et al, 2019 ), patients (Liu et al, 2022b ), employees (Liu et al, 2022c ), and flight attendants (Liu et al, 2022d , e ). It has also been demonstrated that mindfulness is an effective method for coping with COVID-19-related stress (Weis et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the widespread popularity of mobile networks, people are more likely to use mobile phones to obtain health information ( Liu et al, 2022b ). Social media platforms have become an important medium for people to search, share, and discuss information ( Choi and Toma, 2014 ; Muir et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, loving-kindness meditation based on mindfulness meditation does not significantly improve the level of mindfulness ( Chen et al, 2021 ). But loving-kindness meditation can significantly improve people’s sense of social presence ( Liu et al, 2022d ). Mindfulness is a training that helps users to become more present, self-aware, and better able to respond rather than react to everyday situations.…”
Section: Discussionmentioning
confidence: 99%